The Effect of Extrovert-Introvert Personality Types on Consumer Trust on Online Customer at Bekado Mart - Nuralfiah Nuralfiah; Suwarti Suwarti (Proceedings Series on Social Sciences & Humanities, 2021)
This study examines the effect of extrovert-introvert personality types on consumer confidence in online customers at Bekado Mart Purwokerto. This research is a quantitative study with a population of online customers or members of Bekado Mart Purwokerto. The sample used in this study was 500 customers (according to the data of the Bekado Mart admin). The data collection method uses a consumer confidence scale and an extrovert-introvert personality type scale. The sampling system uses an accidental sampling technique carried out using Google Forms in the data collection process. Reliability test using Cronbach alpha. The consumer confidence scale is 38 items. Based on the results of the study, sig. P = 0.000 (p < 0.05) and the coefficient of determination Rsquare = .148. The proposed hypothesis is accepted, namely that the extrovert-introvert personality type influences consumer confidence in online customers at Bekado Mart Purwokerto. The regression results show a positive value, meaning that the extrovert-introvert personality type influences consumer confidence.